Enhancing hydrogen storage performance via optimizing Y and Ni element in magnesium alloy - Xu Pang; Lei Ran; Yu'an Chen; Yuxiao Luo; Fusheng Pan (Journal of Magnesium and Alloys, 2022)
Magnesium-based hydrogen storage materials are considered as one of the most promising candidates for solid state hydrogen storage due to their advantages of high hydrogen capacity, excellent reversibility and low cost. In this paper, Mg91.4Ni7Y1.6 and Mg92.8Ni2.4Y4.8 alloys were prepared by melting and ball milling. Their microstructures and phases were characterized by X-ray diffraction, scanning electron microscope and transmission electron microscope, and hydrogen absorbing and desorbing properties were tested by the high pressure gas adsorption apparatus and differential scanning calorimetry (DSC). In order to estimate the activation energy and growth mechanism of alloy hydride, the JMAK, Arrhenius and Kissinger methods were applied for calculation. The hydrogen absorption content of Mg92.8Ni2.4Y4.8 alloy reaches 3.84 wt.% within 5 min under 350 ℃, 3 MPa, and the maximum hydrogen capacity of the alloy is 4.89 wt.% in same condition. However, the hydrogen absorption of Mg91.4Ni7Y1.6 alloy reaches 5.78 wt.% within 5 min, and the maximum hydrogen absorption of the alloy is 6.44 wt.% at 350 ℃ and 3 MPa. The hydrogenation activation energy of Mg91.4Ni7Y1.6 alloy is 25.4 kJ/mol H2, and the enthalpy and entropy of hydrogen absorption are -60.6 kJ/mol H2 and 105.5 J/K/mol H2, separately. The alloy begins to dehydrogenate at 210 ℃, with the dehydrogenation activation energy of 87.7 kJ/mol H2. By altering the addition amount of Ni and Y elements, the 14H-LPSO phase with smaller size and ternary eutectic areas with high volume fraction are obtained, which provides more phase boundaries and catalysts with better dispersion, and there are a lot of fine particles in the alloy, these structures are beneficial to enhance the hydrogen storage performance of the alloys.